Development of a Fluorescent Rapid Test Sensing System for Influenza Virus - Wei-Chien Weng; Yu-Lin Wu; Zia-Jia Lin; Wen-Fung Pan; Yu-Cheng Lin (Micromachines, 2025)
This paper presents a sensitive and stable fluorescence rapid test sensing system for the quantitative analysis of influenza rapid test results, integrating a detection reader to minimize errors from conventional visual interpretation. The hardware includes a control board, touchscreen, camera module, UV LED illumination, and a dark chamber, while the software handles camera and light source control, as well as image processing. Validation shows strong linearity, high precision, and reproducibility. For influenza A (H1N1), the system achieved a coefficient of determination (R2) of 0.9782 (25–200 ng/mL) and 0.9865 (1–10 ng/mL); for influenza B (Yamagata), the coefficient of determination (R2) was 0.9762 (2–10 ng/mL). The coefficient of variation ranged from 1–5% for influenza A and 4–9% for influenza B. Detection limits were 4 ng/mL for influenza A and 6 ng/mL for influenza B. These results confirm the system’s capability for accurate quantitative analysis while reducing reliance on subjective interpretation. Its compact, portable design supports on-site rapid testing and allows for potential expansion to detect other targets, such as COVID-19, RSV, and myocardial enzymes. The system’s scalability makes it a promising tool for clinical diagnostics, point-of-care testing (POCT), and infectious disease monitoring.